Analisis Pengaruh Kinerja Seorang Pemimpin Terhadap Perekonomian di Indonesia - Apriaman Hulu; Fajar Kristian Harefa; Falsimando Ndruru; John Fiser Harefa; Metodius Bate’e; Vallery Tasa Leora P.S Gulo (Indo Publishing, 2026)
This study aims to analyze the correlation between the effectiveness of national leadership performance and economic stability and growth in Indonesia. In developing countries like Indonesia, the role of central (executive) leadership is a crucial determinant in determining the direction of fiscal, monetary, and infrastructure development policies. The research method used is a descriptive qualitative approach with a literature review of macroeconomic data across various leadership periods. The analysis shows that credible leadership performance has a significant influence on market confidence and the flow of foreign direct investment (FDI). Key variables such as decisiveness in bureaucratic reform, the political stability created, and decision-making ability during times of global crisis are the main drivers of Gross Domestic Product (GDP) dynamics. This study concludes that leadership with a long-term vision can mitigate national economic risks, while less stable leadership tends to lead to market volatility. These findings recommend the need to synchronize leadership vision with the strengthening of economic institutions to create sustainable development that does not rely solely on individual figures